Urbanization and the two tails of malnutrition in Tanzania - Hannah Ameye (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
It is increasingly recognized that urbanization is accompanied by profound changes in African diets. Some studies hold the hope that urbanization will help eradicate hunger and undernourishment, both still prominent issues in the region. Others have warned that urbanization may actually shift the problem from the left to the right tail of the food consumption distribution, with urban diets being dominated by high-calorie processed foods and an excessive intake of oil and sugar. Throughout the literature, most datasets simply provide aggregated nutritional information and lack the necessary level of granularity hampering investigation into these issues. Most studies also aggregate everything from small towns to megacities into a single 'urban' category, potentially missing important heterogeneity with respect to dietary change. This paper overcomes these problems by using a dataset of 1,498 households from Tanzania, each of whom completed a 2-week consumption diary that records detailed information on the quantity and characteristics of all food consumed. This allows us to calculate the macro- and micronutrient content of these diets. Dietary differences across urban and rural households are documented using OLS regressions and the doubly robust estimation method. These analyses are split into separate income groups to account for income heterogeneity. Our results caution against generalizations about urban diets as "right tail" theories have done. Firstly, we observe that the average urban household has a more wholesome diet indicating that micronutrient deficiencies are less prominent. This thus contradicts theories stating that urban diets are unhealthy. On the one hand, low and middle income urban households from our sample area meet the daily recommended values of most nutrients, making their diet more fulfilling compared to that of rural households. On the other hand, rich urban and rural households are found to overconsume, yet urban households tend to be less extreme. Secondly, when disaggregating urban areas into various categories, it is found that secondary towns present favourable diets and although larger cities such as Dodoma and Dar Es Salaam show higher levels of consumption, sufficient micronutrients are taken in and unhealthy substances do not reach alarmingly high levels.
Keywords: 330; Micronutrient Intake; Malnutrition; Urbanization; Secondary Towns; Tanzania